The factors influencing digital entrepreneurship intention: a study on college community student in Kelantan - Siti Marhaini Md Resadi (2021)
The study is applying Theory of Planned Behavior (TPB) which include attitude, subjective norm and perceived behavioral control as a theoretical framework to determine The Factors Influencing Digital Entrepreneurship Intention: A Study on College Community Student in Kelantan. Data are collected through questionnaire. A 20 item cross-sectional survey was administered among the participants. A total of 136 college students participated in the study. The respondent is determined based on simple random sampling technique. Using the structural equation modelling and partial least squares (SEM-PLS) analysis method, researcher found that only two factor: attitude and perceived behavioral control have significant influence on digital entrepreneurship intention. However, subjective norm is non-significant on respondent’s intention to digital entrepreneurship. The findings give educators ideas for how to encourage TVET students to engage in digital entrepreneurship through educational program and training.